(untitled) (Southwestern Research Journal, 2024)
Nepal has experienced changes in socioeconomic characteristics within the past couple of decades. Neoliberal economic policy was adopted after 1990, which has impinged in many aspects of Nepali society. This article explicates the consequences of politieconomic practices of neoliberalism and globalization, which have changed different variables of social structure with the changes of socio-economic characteristics with the mode of production. It has to be analyzed critically and explicate the consequences of neo-liberalism and globalization that has to assess the extent of change through the anthropological perspective. This study is prepared based on historical materialist perspective and neo-liberalism. The article is based on an ethnographic study of the urbanizing society of multicultural and diversified individuals located in the inner-Tarai mid-Nepal, where indigenous groups and the ethnicities of inland migrants have been residing since time immemorable. This paper is prepared for evaluating the period before and after the implementation of neo-liberalism based on the qualitative primary data taken myself. I have analyzed how the landholding system and pattern of landownership are changing; how most of the workforce have changed their occupation from traditional to non-traditional; how the class structure is changing from peasant to labor; how the mode of production is changing from feudalistic to capitalistic; and what are the driving factors of change in societies. I have concluded that due to the socio-economic practices of neo-liberalism and globalization, independent peasants have become proletarians in the single system of the global economy, though they seem like the middle class in the domestic context.